Transforming Homoeopathic Education: The Impact of NCH Reforms (Homoeopathy for All, 2025)
In recent years, the field of  Homoeopathy in India has undergone  significant transformation, primarily  driven by the establishment of  the National Commission for  Homoeopathy (NCH) in 2020.  This regulatory body, created  under the National Commission  for Homoeopathy Act 2020, has  spearheaded a series of reforms  aimed at enhancing the quality and  integrity of Homoeopathy education  and practice. These changes  promise to elevate the standards  of Homoeopathy, ensuring its  practitioners are well-equipped  to meet contemporary healthcare  challenges.
Keywords: field; establishment; spearheaded; integrity; practitioners